The Effectiveness of Augmented Reality in Improving Elementary School Students' Science Literacy: A Systematic Literature Review - Rizka Septiana; Rohmani Rohmani (Pedagogy Review, 2026)
Science literacy among primary school pupils remains low, largely due to conventional teaching approaches and challenges in understanding abstract scientific concepts. Augmented Reality (AR) provides an interactive and engaging learning experience that helps make these concepts more concrete. Although numerous studies have highlighted the potential of AR in science education, systematic reviews examining its effectiveness in improving science literacy among primary school pupils are still limited. This study aims to analyze the effectiveness of AR in improving primary school pupils’ science literacy, identify the characteristics of existing research, and examine the challenges of its implementation in learning. The study employed a Systematic Literature Review (SLR) method following the PRISMA guidelines. Data were obtained from the Google Scholar and Scopus databases for the period 2021–2025 using the keywords “Augmented Reality” and “science literacy” and “primary school”. Inclusion criteria included research articles relevant to the topic, focusing on primary school pupils, available in full text, and indexed in Scopus or at least SINTA 3. Following the process of identifying, screening, and selecting articles, 10 articles that met the criteria were identified and systematically analyzed. Data were extracted using a pre-defined extraction form capturing details such as study design, AR type, sample characteristics, measured variables, and key findings. Subsequently, extracted data were synthesized using thematic analysis to identify recurring patterns, challenges, and optimal implementation strategies across the selected studies. The results indicate that AR is effective in improving students’ science literacy by enhancing their understanding of scientific concepts, motivation and engagement in learning, scientific process skills, and 21st-century skills, which include critical thinking, creativity, collaboration, and communication (the 4Cs). Furthermore, the effect of AR tends to be more optimal when integrated with innovative learning models, such as inquiry-based and discovery learning. However, the implementation of AR still faces several challenges. These include limitations in technological facilities and teacher competence. Consequently, AR is a promising teaching tool for supporting the science literacy of primary school pupils and, as such, requires support in the form of adequate facilities and professional development for teachers.Keywords: Augmented reality, Scientific literacy, Elementary school, Systematic literature review